2525. Understanding PrEP in Female Adolescents: A Parent/Adolescent Dyad Perspective - Shah, Meera (Open Forum Infect Dis, 2019)
BACKGROUND: Adolescents aged 13–24 years account for 23% of HIV diagnoses in the Atlanta Metropolitan Area, indicating the need for new prevention strategies. Pre-Exposure Prophylaxis (PrEP), recently approved for adolescent use, is effective in HIV prevention and is often marketed to young men who have sex with men (MSM); however, problems with access, scalability and waning adherence have limited its use in this population and more broadly. A 2016 CDC HIV surveillance report showed 19.2% of new HIV diagnoses were attributed to heterosexual transmission in women aged 13–24, relative to 0% in their heterosexual male counterparts, and 5.4% in same-aged MSM. This study assesses parent and female adolescent knowledge on HIV risk and PrEP perception to inform potential implementation strategies. METHODS: PrEP acceptability and barrier surveys were administered to 102 adolescent-parent dyads attending an adolescent clinic and emergency room in Atlanta, Georgia. Eight female adolescent-parent pairs were randomly selected to participate in in-depth phone interviews. Responses were analyzed using computer-assisted thematic analyses. RESULTS: Of the 8 female adolescent participants (mean age = 18.9 years), all were African American, and 1 was sexually active. Of the 8 parent participants (mean age = 44.1 years), all were female and African American. None of the participants had ever used PrEP. Analysis indicated that both parents and adolescent females had poor HIV risk assessment and knowledge, as well as barriers to PrEP usage including concerns about side effects, cost, and desire for alternative PrEP delivery methods and/or schedules. Finally, adolescent females expressed reliance on self-efficacy to be able to discuss HIV protection methods with their partner. CONCLUSION: Female adolescents use unreliable methods to ensure HIV prevention, and with poor HIV knowledge, are at risk of transmission. Thus, PrEP may be a viable option for adolescent females at high risk for infection. PrEP implementation strategies in adolescents needs to consider HIV risk assessment, PrEP education, potential options for alternative dosing and delivery, and continued implementation work, focused beyond just the young MSM community. DISCLOSURES: All authors: No reported disclosures.